Diagnostic Challenge: A Report of Two Adult-Onset Still's Disease Cases - Sakunee Niranvichaiya; Daranporn Triwongwaranat (Hindawi Limited, 2017)
This study reports two adult-onset Still's disease (AOSD) cases that met both Yamaguchi's and Fautrel's criteria and that presented with notable clinical manifestations. One case presented with atypical dermographism-like rash with an extremely high ferritin level. The other case presented with typical salmon-pink maculopapular rash but had atypical positive rheumatoid factor. This suggests that although negative rheumatoid factor is one of the criteria used for the diagnosis of AOSD, a positive rheumatoid factor result does not exclude AOSD. Beside a classic rash, characterized by transient salmon-pink maculopapular rash, we also find atypical dermographism-like rash. These findings remind us that there exist various types of rash from AOSD.